PRELIMINARY RESULTS FROM RADON OBSERVATION AT SYOWA STATION, ANTARCTICA, DURING 1996 - ウイ, ヒロタカ; タサカ, シゲキ; ハヤシ, マサヒコ; オサダ, カズオ; イワサカ, ヤスノブ; UI, Hirotaka; TASAKA, Shigeki; HAYASHI, Masahiko; OSADA, Kazuo; IWASAKA, Yasunobu (National Institute of Polar Research, 1998)
P(論文) The concentration of ^<222>Rn in surface air was measured for the first time at Syowa Station, Antarctica in the period September 1996-January 1997 by an electrostatic collection method. The concentration of ^<222>Rn was higher in the first half than the latter half of the monitoring period. Daily mean ^<222>Rn concentration averaged 270mBq/m^3 for the first half of the period and 150mBq/m^3 for the latter half of the period. The maximum daily mean ^<222>Rn concentration was 630mBq/m^3,and the minimum concentration was 70mBq/m^3. The daily mean values were higher than those measurement in previous studies in Antarctica. Remarkable ^<222>Rn concentration increases (radon storms), which accompanied cyclones, were observed twice during the austral spring at Syowa Station. The first radon storm occurred on 18-21 September and the second on 16-20 October 1996. The daily mean ^<222>Rn concentrations in the first and second radon storms attained 530mBq/m^3 and 630mBq/m^3 respectively. On the other hand, the hourly mean ^<222>Rn concentration attained 1200mBq/m^3 in the second event. This implies that the ^<222>Rn concentrations vary on a short time scale. The main feature of the ^<222>Rn concentration record corresponds to intense mixing of air masses from mid-latitude continents to Antarctica. This implies that the variations of ^<222>Rn may be related to the wind direction. The concentrations of ^<222>Rn seem to increase with southerly wind and decrease with northerly or northeasterly wind. departmental bulletin paper